Kelarutan Zat Warna Organik dalam Gelasi Mikroemulsi Water In Oil Sistem Air, Surfaktan Nonionik Tween 60 dan Sikloheksana - Aulia Rahmi; Hary Sanjaya; Fitri Amelia; Ananda Putra (Departemen Kimia FMIPA UNP, 2022)
Organic dyes can be dissolved in the gelation of water in oil (w/o) microemulsion of the system of water (pH=4,5 and pH=9,5), nonionic surfactan tween 60 and cyclohexane. The purpose of this study was to prepare microemulsion gels using the sol-gel method, determine the solubility of organic dyes (turmeric and telang flower) in gelation, determine the value of density, refractive index of organic dyes in gelation microemultion (w/o) of the system of water, nonionic surfactan tween 60 and cyclohexane. Gel preparation was carried out using the sol-gel method at a temperature low using TEOS and ethanol which is hidrolyzed with water to form gel. Tetra ethyl ortho silicate which is added 1: 8 mol comparison to the amount of water in microemilsion of water in oil. Determination of value of the refractive index in this study using an ABBE refractometer. The result showed that the solubility of dye organic matter from turmeric and telang flower was 1,376% and 0,498% at pH 4,5 and 1,292% and 0,468% at pH 9,5. The density can be seen by the density test with the result of greatest density density is tumeric 0,87744 g/cm3 at pH 4,5 and 0,86836 g/cm3 at pH 9,5. Then measure the refractive index value, namely turmeric 1,4154 at pH 4,5 and 1,4274 at pH 9,5.